POSTULATES, PRINCIPLES AND RESEARCH IN ACCOUNTING. - Gordon, Myron J. (The Accounting Review, 1964)
The article focuses on a criterion for choice among alternative accounting principles, argue the merits of the criterion, and suggest how it may be used. In other words it does not present the results of research on accounting principles, it only proposes a method for carrying out the research. Many accountants are more interested in establishing accounting principles than in considering how one goes about doing so. In fact, some accountants merely state "correct" principles with little or no effort at substantiating their correctness. Confining to questions of research methodology, the author may therefore call for some justification. This justification will be provided by beginning with a review of an important recent effort at establishing the principles of accounting that should be used as a basis for financial statements. In 1959 the American Institute of Certified Public Accountants created an Accounting Principles Board, which would be the sole group within the Institute having authority to make or authorize pronouncements on accounting principles.